Biomechanics of longswings preceding tkachev on uneven bars - Manning, M. L.; Irwin, G.; Kerwin, D. G. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
Changes in the rules governing the separation of uneven bars have allowed female gymnasts to perform the Tkachev in both directions. The aim of this study was to compare the similarities in the preparatory longswing during the outward (O) and inward (I) Tkachevs. Video recordings of the Tkachevs (O=5, I=5) were collected from the 2000 Sydney Olympic Games. A 37° greater range of movement was found at the hips during the I Tkachev. In the more conventional O technique changes in the hip angle were smaller (23°) and occurred over a greater circle angle. This study has identified differences in what appear to be very similar skills. Further inter-segmental coordination and joint kinetic analyses may provide insight into the performance of these release and regrasp skills.